2008
DOI: 10.1073/pnas.0711175105
|View full text |Cite
|
Sign up to set email alerts
|

CD73 is required for efficient entry of lymphocytes into the central nervous system during experimental autoimmune encephalomyelitis

Abstract: CD73 is a cell surface enzyme of the purine catabolic pathway that catalyzes the breakdown of AMP to adenosine. Because of the strong immunosuppressive and antiinflammatory properties of adenosine, we predicted that cd73 ؊/؊ mice would develop severe experimental autoimmune encephalomyelitis (EAE), an animal model for the central nervous system (CNS) inflammatory disease, multiple sclerosis. Surprisingly, cd73 ؊/؊ mice were resistant to EAE. However, CD4 T cells from cd73 ؊/؊ mice secreted more proinflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
199
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(212 citation statements)
references
References 44 publications
(54 reference statements)
11
199
2
Order By: Relevance
“…A 1 AR-KO mice developed a severe form of EAE with extensive damage in CNS, and activation of A 1 AR with agonist adenosine amine congener attenuated demyelination in EAE mice (6). Recently, mice with a genetic deficiency of CD73, an enzyme critical for the generation of extracellular adenosine, were unexpectedly found to be highly resistant to EAE (9). The authors also found A 2A AR antagonist SCH58261 protected mice from CNS injury in EAE.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A 1 AR-KO mice developed a severe form of EAE with extensive damage in CNS, and activation of A 1 AR with agonist adenosine amine congener attenuated demyelination in EAE mice (6). Recently, mice with a genetic deficiency of CD73, an enzyme critical for the generation of extracellular adenosine, were unexpectedly found to be highly resistant to EAE (9). The authors also found A 2A AR antagonist SCH58261 protected mice from CNS injury in EAE.…”
Section: Discussionmentioning
confidence: 78%
“…It seems adenosine might act mainly through A 1 AR and A 2A AR to suppress inflammation. However, a recent study unexpectedly discovered that mice with a genetic deficiency in CD73, a nucleotidase critical for the generation of extracellular adenosine, are highly resistant to myelin oligodendrocyte glycoprotein (MOG)-induced brain and spinal cord injury (9), indicating a proinflammatory function of adenosine.…”
Section: Ultiple Sclerosis (Ms) Is a T Cell-mediated Autoimmune Dismentioning
confidence: 99%
“…In contrast to its role in lymph nodes, CD73 promotes T-cell extravasation in peripheral tissue. Accordingly, decreased extravasation of pathogenic T cells was recently suggested as the cause of resistance of CD73-deficient mice to experimental autoimmune encephalomyelitis (Mills et al, 2008). Through the production of adenosine and the activation of adenosine receptors on endothelial cells, it was suggested that CD73 triggers adhesion molecules, such as intercellular adhesion molecule 1 on endothelial cells.…”
Section: Cd73 (Ecto-5mentioning
confidence: 99%
“…Accordingly, knockdown of lipid raft-associated protein, caveolin-1, in ECs was shown to inhibit transendothelial leukocyte migration [93]. Recent studies using peripheralderived endothelium and epithelial cultures have identified novel molecules that coordinate leukocyte transmigration, including JAMs, CD44, CD47, CD73 [94], CD90 [95], CD137 [96], CD81 [97], CD99 [98], CD99L, and CD166/ ALCAM [99]. Most of these adhesion molecules are enriched in lipid rafts derived from primary cultures of human BECs [99].…”
Section: Adhesion Raftsmentioning
confidence: 99%